Ba3[Rh(OH)6]2 ⋅ H2O – a Precursor to Barium Oxorhodates with One-dimensional Hydrogen Bonding Systems - Albrecht, Ralf; Bretschneider, Vincent; Doert, Thomas; Ruck, Michael (Zeitschrift für Anorganische und Allgemeine Chemie, 2021)
Orange-colored single-crystals of barium hexahydroxo-rhodate(III) monohydrate, Ba3[Rh(OH)6]2 ⋅ H2O, were synthesized in a PTFE-lined autoclave at 200 °C starting from Ba(NO3)2, RhI3 and concentrated sodium hydroxide solution (water-base ratio 4 : 1). Single-crystal X-ray diffraction revealed the triclinic space group (Formula presented.) (no. 2) with lattice parameters a=824.60(6) pm, b=852.78(5) pm, c=885.34(6) pm, α=94.294(3)°, β=92.422(3)°, γ=91.673(3)° at 100(1) K. The crystal structure consists of [Rh(OH)6]3− octahedra surrounded by barium cations and water molecules. Hydrogen bonds with a wide range of donor-acceptor distances are located between hydroxide groups and water molecules to form one-dimensional hydrogen bonding networks in c direction. Upon heating in air, Ba3[Rh(OH)6]2 ⋅ H2O decomposes first to “BaRhO3” with a superstructure of the hexagonal perovskite type, which undergoes a phase transition to the 2H hexagonal perovskite Ba9Rh8O24 above 900 °C.
CRIS-Team Scopus Importer:2022-04-14
Keywords: crystal structure; hydroflux synthesis; rhodium; spectroscopy; thermal analysis